Relationship between spiritual health and hope by dietary adherence in haemodialysis patients in 2018 - Motahareh Musavi Ghahfarokhi; Sara Mohammadian; Bahar Mohammadi Nezhad; Maryam Kiarsi (Wiley, 2020)
Abstract Aim The present study aimed to determine the relationship between spiritual well‐being and hope through adherence to diet in haemodialysis patients referred to the dialysis centre. Design This research was a cross‐sectional study of a descriptive‐analytical type conducted on 120 patients undergoing haemodialysis in a haemodialysis centre of a hospital affiliated to Dezful University of Medical Sciences using the census method. Method The data were collected using a questionnaire and through the laboratory information included in the patient's records. The data collection tools were a demographic information questionnaire, the Ellison and Paloutzian spiritual well‐being scale (SWBS), the Hope‐Herth questionnaire and the objective laboratory criteria (phosphorus, potassium). This included the weight difference between the two dialysis sessions from the record to examine the adherence to the diet. Results The results indicate there to be a significant relationship between hope and spiritual well‐being with the objective criteria of the adherence to the diet in dialysis patients (p = .001).